The Effects of a Family Management-Enhancing Program on The Caregivers’skill of An Early Mobility of Stroke Patients - Junsree, Visunee; liangchawengwong, Sunthara; Muengtaweepongsa, Sombat (Journal of The Royal Thai Army Nurses, 2020)
This quasi-experimental and time series research aimed to study the effects of a family management enhancing program on the caregivers’ skills of an early mobility among stroke patients. Purposive selection and thirty-six caregivers were separated in an intervention and control group. The research instruments comprised of the early mobility family management Program, the Booklet and symbolic modeling VDO. Data collection used the Caregiver Characteristics Data, Early Mobility Caring Skill of ADL and RMI. The contents validity of the instruments were tested by five experts = 0.90-0.93 and Cronbach’s alpha reliability test revealed 0.88 to 0.93. Data were analyzed using descriptive statistics, the chi-squares test, the Friedman test, repeated measures ANOVA, and Bonferroni test The results revealed: 1) The mean score for the early mobility caring skills of ADL and RMI in both groups during the 1, 4, and the 8 week were increase significantly (p<.001) 2) Compared between the intervention and control group, the results revealed that the mean score for the early mobility caring skill of ADL and RMI at the 1 week was not differently, but between the 4 and the 8 week were different significantly (p<.001). The family management model and indicate that it can be used to develop the mobility skills of caregiver and help with the early mobility